2017
DOI: 10.21448/ijsm.369775
|View full text |Cite
|
Sign up to set email alerts
|

Investigating of Phytochemicals, Antioxidant, Antimicrobial and Proliferative Properties of Different Extracts of Thymus spathulifolius Hausskn. and Velen. Endemic Medicinal Plant from Sivas, Turkey

Abstract: Thymus species has been used for antioxidant, antiseptic, antitussive, carminative, anti-inflammatory and antimicrobial activities as well as tonic and herbal teas. The present study was conducted to evaluate antioxidant, antimicrobial and proliferative properties of ethanol crude extract and fractions of Thymus spathulifolius (Hausskn. and Velen.) herbes. The antioxidant properties of ethanol extracts and fractions of Thymus spathulifolius were investigated using 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The beneficial medicinal effect of a plant is due to the secondary metabolites in the plant [50][51][52][53]. There are alkaloids, flavonoids and phenolic compounds in the methanol extract of E. khuzistanicum flower according to GC/MS analysis that similar results have been described by Tiwari et al (2011) [50].…”
Section: Discussionsupporting
confidence: 59%
“…The beneficial medicinal effect of a plant is due to the secondary metabolites in the plant [50][51][52][53]. There are alkaloids, flavonoids and phenolic compounds in the methanol extract of E. khuzistanicum flower according to GC/MS analysis that similar results have been described by Tiwari et al (2011) [50].…”
Section: Discussionsupporting
confidence: 59%
“…In addition, H 2 O 2 -induced oxidative stress has been reported as an alternative to study the antioxidant activities of plant extracts in cells [31]. Previous studies on different Thymus species have shown that this plant imparts antioxidant effects that play a crucial role in healing process by protecting cells from oxidative damage caused by free radicals [32,33,34,35]. In the present study, the protection degrees of TS extracts against oxidative stress were differed in H 2 O 2 -treated cells, both in the co-treatment and pre-treatment protocols, and this may explain the possible mechanism of antioxidant effect.…”
Section: Resultsmentioning
confidence: 99%
“…The in vitro cytotoxic activities of the extracts were evaluated by the MTT colorimetric assay according to Mosmann (1983) and Eruygur et al (2017). Prostate cancer (PC3) cell lines with exponential growth were planted into 96-well microplates at a density of 5×10 3 cells per well in 100 μL of culture medium and allowed to adhere for 16 hours before being cultured at 37°C in a 5% CO2 humidified environment.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%